Peran Komunikasi Guru Pendidikan Agama Islam Dalam Pembinaan Akhlak Siswa SMP Negeri 36 Makassar - Sultan, Ahmad Riyadi; Setiawati, Nur; Hasriani, Andi (Universitas Muslim Indonesia, 2021)
This research aims to know the communication role of Islamic Religious Education Teachers in fostering the morals of seventh grade students of SMP Negeri 36 Makassar and to know the inhibiting factors of the communication role of Islamic Religious Education Teachers in fostering the morals of seventh grade students of SMP Negeri 36 Makassar. This research is a qualitative research at SMP Negeri 36 Makassar. Data was collected using several methods, namely observation, interviews, and documentation. The sources of data and the subject of this research are Islamic Religious Education Teachers and Class VII Students of SMP Negeri 36 Makassar in 2021. Data analysis was carried out in four stages, namely data collection and checking, data reduction, data presentation, and drawing conclusions. The results of this study indicate that (1). The researcher sees that the communication of Islamic religious education teachers plays a very important role in fostering the morals of seventh grade students of SMP Negeri 36 Makassar because in the learning process there are factors that influence each other. Communication is carried out normally so that both parties are educated on each other. When communicating, a person will experience changes in behavior from not knowing to knowing, and not understanding to understanding and those who do not have good character to have good character. Thus, communication can have an effect in accordance with the expected goals, namely fostering students' morals so that these students have commendable morals. (2). Factors inhibiting the role of teacher-student communication in moral development in Islamic Religious Education Subjects for class VII SMP Negeri 36 Makassar in 2021 include: a. The ability of students to speak Indonesian is still weak and correct. b. Lack of Learning Media; c. Different student abilities; d. Online learning